2023
DOI: 10.3390/cancers15143712
|View full text |Cite
|
Sign up to set email alerts
|

Grade Progression and Intrapatient Tumor Heterogeneity as Potential Contributors to Resistance in Gastroenteropancreatic Neuroendocrine Tumors

Abstract: Gastroenteropancreatic neuroendocrine neoplasms (NENs) are a heterogenous group of tumors that are incurable when metastatic, regardless of grade. The aim of this article is to understand tumor heterogeneity and grade progression as possible contributors to drug resistance in gastroentropancreatic neuroendocrine tumors (GEP-NETs). Heterogeneity has been observed in the genetic, pathological, and imaging features of these tumors at baseline. Diagnostic challenges related to tumor sampling and the potential for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 92 publications
(197 reference statements)
0
1
0
Order By: Relevance
“…Current studies based on next-generation sequencing (NGS) interpretation have shown that tumor variant burden (TMB) in synchronous and metachronous metastatic samples (liver and lymph nodes) is sometimes different from that of the primary tumor (pancreas). Analysis of the clonal and subclonal architecture and genetic pro le suggests that most metastatic subclones could be traced back to the initial tumor [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Current studies based on next-generation sequencing (NGS) interpretation have shown that tumor variant burden (TMB) in synchronous and metachronous metastatic samples (liver and lymph nodes) is sometimes different from that of the primary tumor (pancreas). Analysis of the clonal and subclonal architecture and genetic pro le suggests that most metastatic subclones could be traced back to the initial tumor [21,22].…”
Section: Discussionmentioning
confidence: 99%